2021
DOI: 10.1002/jbt.22961
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of rosmarinic acid against azoxymethane‐induced colorectal cancer in rats

Abstract: Colorectal cancer (CRC) incidence is increasing gradually and has been become one of the most common cancers worldwide. Hence, it is important to discover cheap, naturally occurring compounds to be effective in suppressing the devastating effect of colonrelated tumors. Rosmarinic acid (RA), one of the compounds of plant origin, possesses attractive features for use as an agent for cancer prevention and treatment. This study investigated the ability of RA to prevent azoxymethane (AOM)-induced rat colon carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Ilhan et al showed in their study that there was a significant increase in TAS levels of the group receiving rosmarinic acid [26][27] . However, in this study, we found that there was no statistically significant difference as a result of the evaluation of TAS levels in both tissue and serum.…”
Section: Discussionmentioning
confidence: 99%
“…Ilhan et al showed in their study that there was a significant increase in TAS levels of the group receiving rosmarinic acid [26][27] . However, in this study, we found that there was no statistically significant difference as a result of the evaluation of TAS levels in both tissue and serum.…”
Section: Discussionmentioning
confidence: 99%
“…RA/ZnO/chitosan nanoparticles exhibited high efficiency in combating methamphetamine elevation in casp3a mRNA levels and oxidative changes. Ilhan et al ( 2022 ) reported protective effects of azoxymethane-induced rat colon carcinogenesis and anti-oxidant/oxidant balance. Fuster et al ( 2021 ) formulated RA-loaded silk-fibroin nanoparticles to investigate the anti-tumor potential in human cervical and breast cancer cells.…”
Section: Pharmacological Properties Of Ramentioning
confidence: 99%
“…In AOM and dextran sulfate sodium-induced colorectal carcinogenesis animal models, interleukin-6 (IL-6) levels and progression of colitis-associated colon cancer were decreased by RA. The mechanism involved the downregulation of Toll-like receptor 4 (TLR4)/nuclear factor-κB (NF-κB) and signal transducer and activator of transcription 3 (STAT3) [ 9 , 79 ]. RA prevents colorectal carcinogenesis due to antioxidation and anti-inflammatory effects.…”
Section: Biological Processes and Mechanism Of Action Of Ra In Tumor ...mentioning
confidence: 99%
“…In addition, RA attenuated DMH-induced upregulation of cytochrome P450 (CYP450) [ 74 , 77 ]. Second, RA inhibited the release of TNF-α, IL-6, and COX-2 pro-inflammatory factors [ 76 , 79 ]. The anti-inflammatory effect of RA has been related to the inhibition of TLR4/NF-κB and STAT3 [ 9 ].…”
Section: Prevention Of Ra In Tumorigenesismentioning
confidence: 99%